Comparative Efficacy of Topical Calcipotriol (0.005%) Versus Topical Corticosteroid (Betamethasone 0.1%) in Treating Plaque Type Psoriasis - Ahmed, Gulam Kazem Ali; Khandker, Lubna; Nessa, Moriom; Alam, Mohd Nurul; Chakraborty, Anjana; Yeasmin, Farhana (Medicine Today, 2015)
A clinical trial was carried out to compare the efficacy of topical calcipotriol (0.005%) and topical corticosteroid (betamethasone 0.1%) in the treatment of plaque type psoriasis. The study was conducted from January 2012 to August 2012 and patients of plaque type psoriasis attending outpatient department of Dermatology and Venereology, Bangabandhu Sheikh Mujib Medical University, Dhaka were the study population. Patients were divided into two groups, group A was treated with topical calcipotriol (0.005%) ointment and group B with topical corticosteroid (betamethasone 0.1%) ointment. The mean baseline PASI score was 6.7 ±4.5 and after 8 weeks, the mean PASI score was 2.0 ±1.4 for group A and mean baseline PASI score was 5.5 ±4.2 and after 8 weeks, the mean PASI score was 2.5 ±1.4 for group B. There was statistically significant reduction in PASI score from base line after 8 weeks of treatment in both treatment groups (p < 0.001). After 8th week of treatment moderate response was 11(73.3%) in group A and 9(60%) in group B. Very good response was 4 (26.7%) in group B and 2 (13.3%) in group A and minimal response of treatment occurs equally 2 (13.3%) in group A and group B. In the light of the findings of the study we conclude that each of the treatment of calcipotriol(0.005%) and betamethasone (0.1%) is individually effective. Further multicenter, randomized, double-blind study should be conducted with large sample size. Medicine Today 2014 Vol.26(2): 88-94